Combination of Nanomicellar Technology and In Situ Gelling Polymer as Ocular Drug Delivery System (ODDS) for Cyclosporine-A - Eleonora Terreni; Erica Zucchetti; Silvia Tampucci; Susi Burgalassi; Daniela Monti; Patrizia Chetoni (MDPI AG, 2021)
A combination of in situ gelling systems and a loaded drug self-assembling nanomicellar carrier was chosen in this study as a new potential Ocular Drug Delivery System (ODDS) for Cyclosporine-A (CyA), a poorly water-soluble drug. Two non-ionic surfactants (d-α-tocopherol polyethylene glycol succinate, VitE-TPGS and polyoxyl 40 hydrogenated castor oil, RH-40) were used to produce the nanomicelles. The physical-chemical characterization of the nanomicelles in terms of CyA entrapment (EE%) and loading efficiency (LE%), cloud point (CP), regeneration time (RT), size and polydispersity index (PI) allowed us to select the best combination of surfactant mixture, which showed appropriate stability, high CyA-EE (99.07%), very small and homogeneous dimensions and favored the solubilization of an amount of CyA (0.144% w/w) comparable to that contained in marketed emulsion Ikervis®. The selected nanomicellar formulation incorporated into optimized ion-sensitive polymeric dispersions of gellan gum (GG-LA: 0.10, 0.15 and 0.20% w/w) able to trigger the sol-gel transition after instillation was characterized from technological (osmolality, pH, gelling capacity, rheological behavior, wettability, TEM and storage stability at 4 and 20 °C) and biopharmaceutical points of view. This new combined approach allowed us to obtain clear aqueous dispersions that were easy to instill and able to form a viscous gel when in contact with the tear fluid, improving CyA ocular bioavailability. Furthermore, this new ODDS prevented CyA transcorneal permeation, exhibited low cytotoxicity and prolonged the CyA resident time in the precorneal area compared to Ikervis®.